Is There a Case for Mandatory Reporting of Racism in Schools? - Auld, Glenn (The Australian Journal of Indigenous Education, 2017)
This paper explores how the colonial hegemony of racism in Australia could be disrupted in schools by introducing mandatory reporting of racism by teachers in Australia, and addresses the benefits and risks of mandatory reporting of racism. Using Aboriginal and Torres Strait Islanders as a case study, the ongoing prevalence of racism in schools is established. I then draw on the literature associated with teachers’ mandatory reporting of child abuse and neglect to construct racism as a form of emotional abuse of children. The complexity of racism as evidenced from the literature limits the mandatory reporting to interactional racism by teachers as an antiracist practice. The justification for mandatory reporting covers the emotional stress caused by racism to students and can also be extended to support Aboriginal and Torres Strait Islander staff in schools. The evidence of learning success where antiracism strategies have been introduced in schools, the opportunity to normalise bystander antiracism by teachers, and the alignment of this reporting initiative with the professional standards of teachers together support a case for mandatory reporting of racism in schools. The arguments against mandatory reporting of racism draw on the generative practices of teachers integrating antiracist discourses in schools.